GNN is a self-glucosylating protein involved in the initiation step of glycogen biosynthesis in Neurospora crassa - de Paula, R. M.; Wilson, W. A.; Terenzi, H. F.; Roach, P. J.; Bertolini, M. U. (Elsevier B.V., 2005)
The initiation of glycogen synthesis requires the protein glycogenin, which incorporates glucose residues through a self-glucosylation reaction, and then acts as substrate for chain elongation by glycogen synthase and branching enzyme. Numerous sequences of glycogenin-like proteins are available in the databases but the enzymes from mammalian skeletal muscle and from Saccharomyces cerevisiae are the best characterized. We report the isolation of a cDNA from the fungus Neurospora crassa, which encodes a protein, GNN, which has properties characteristic of glycogenin. The protein is one of the largest glycogenins but shares several conserved domains common to other family members. Recombinant GNN produced in Escherichia coli was able to incorporate glucose in a self-glucosylation reaction, to trans-glucosylate exogenous substrates, and to act as substrate for chain elongation by glycogen synthase. Recombinant protein was sensitive to C-terminal proteolysis, leading to stable species of around 31 kDa, which maintained all functional properties. The role of GNN as an initiator of glycogen metabolism was confirmed by its ability to complement the glycogen deficiency of a S. cerevisiae strain (glg1 glg2) lacking glycogenin and unable to accumulate glycogen. Disruption of the gnn gene of N. crassa by repeat induced point mutation (RIP) resulted in a strain that was unable to synthesize glycogen, even though the glycogen synthase activity was unchanged. Northern blot analysis showed that the gnn gene was induced during vegetative growth and was repressed upon carbon starvation. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: glycogen; glycogenin; repeat induced point mutation; gene expression; Neurospora crassa; yeast complementation